The association between major dietary patterns and severe mental disorders symptoms among a large sample of adults living in central Iran: Baseline data of YaHS-TAMYZ cohort study - Shamim Shams-Rad; Reza Bidaki; Azadeh Nadjarzadeh; Amin Salehi-Abargouei; Barbora de Courten; Masoud Mirzaei (BMC, 2022)
Abstract Background The diet's role in developing psychological disorders has been considered by researchers in recent years. Objective To examine the association between major dietary patterns and severe mental disorders symptoms in a large sample of adults living in Yazd city, central Iran. Methods This cross-sectional study used the baseline data of a population-based cohort study (Yazd Health study: YaHS). Dietary intakes were assessed by a multiple-choice semi-quantitative food frequency questionnaire (FFQ, Yazd nutrition survey called TAMYZ). Psychological assessments were also done by using the depression, anxiety, and stress scale-21 (DASS-21) questionnaire. Major dietary patterns were identified using principal component analysis (PCA). Analysis of covariance (ANCOVA) and logistic regression analyses were used to evaluate the relationship between dietary patterns and mental disorders symptoms. Results A total of 7574 adults were included in the current analysis. Four major dietary patterns were identified: "Sugar and Fats", "Processed Meats and Fish", "Fruits" and "Vegetables and Red Meat". After adjustment for all confounding variables, participants in the fifth quintile of "Fruits" dietary pattern which was highly correlated with dried fruits, canned fruits, fruit juice, olive, hydrogenated fats and fruits intake, had a lower odds of severe depression (OR=0.61, 95% CI: 0.45-0.81, p for trend=0.057), anxiety (OR=0.64, 95% CI: 0.50-0.80, p for trend=0.007), and stress, (OR=0.45, 95% CI: 0.30-0.68, p for trend=0.081). Conclusions The intake of a dietary pattern high in dried fruits, canned fruits, fruit juice, olive, hydrogenated fats, and fruits might be inversely associated with depression, anxiety, and stress symptoms. Future prospective studies are needed to warrant this finding.